Perancangan Kios Buku Online Dengan Menerapkan Algoritma MD5 Dalam Pengamanan Record Login - Lahagu, Amin Setiawan; Hutahaean, Harvei Desmon (LPPM UNIKA Santo Thomas Medan, 2017)
Online book stall is one form of e-commerce in cyberspace, all the time the sale and purchase transactions of books can be done at any time, but along with the development of online transactions, data controls should also be improved. To avoid data from damage caused by irresponsible people, it is necessary to secure data by applying cryptography to the data. In modern times there are many methods or algorithms that can be used to protect and control data from various attacks, but each of these algorithms certainly has its own weaknesses and strengths. The need for long-distance transactions and the importance of data security caused developers to continue to develop cryptography. MD5 algorithm is a one-way hash function that is often used in cryptography, especially in web-based transactions. The MD5 algorithm encodes data in a constant form of 32 bits. All processes from sales and purchase transactions in online bookstores will be safe and durable when the bookstore database is designed in such a way. The book stall database records are encoded with the MD5 algorithm, especially for logging records as a gateway for hackers or hackers to infiltrate. All transactions in the online book kiosk system are detected by the database, the resilience of the database from all attacks is the control of the system from all kinds of damage.